Optimization Of Uks, Library, And Counseling Guidance Services In Supporting Student Development At Sdit Nur Hidayah Surakarta - Intan Kurniawati; Muhammad Zainudin (STEBIS Bina Mandiri, 2026)
Educational support services, such as School Health Services (UKS), libraries, and Guidance and Counseling (BK), play a crucial role in supporting the physical, intellectual, social, and emotional development of students in elementary schools. However, the implementation of these three services still faces various challenges that can impact their effectiveness in supporting the educational process. This study aims to describe the implementation of UKS, library, and Guidance and Counseling services at SDIT Nur Hidayah Surakarta and identify the obstacles encountered in their implementation. The study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews with UKS staff, library managers, and BK teachers, as well as documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that UKS services have been running well through the promotion of clean and healthy living habits, basic health services, and collaboration with the Community Health Center (Puskesmas). Library services contribute to improving literacy culture through various programs, such as the Library Award and classroom reading corners. Meanwhile, BK services support students' personal, social, and academic development through a humanistic approach and collaboration with homeroom teachers and parents. Despite this, challenges remain, including limited facilities, inadequate staffing, and suboptimal use of technology in library management. This study concludes that these three services have made a positive contribution to student development, but require strengthening facilities, improving human resource competencies, and optimizing technology-based management to ensure more effective and sustainable educational support services.